Fresno Merced Counties Legal Services Staff at Roger Rocka's Guys and Dolls Show - Watkins, Howard::::::::: (1981)
Michael Kanz, Carolyn Phillips, ? Cajiga, George Cajiga, David Cisneros, Cindy Calvert at table